HOUT-12. RETURN TO WORK FOLLOWING AWAKE SURGERY FOR GLIOMAS IN SPEECH-ELOQUENT AREAS. (11th November 2019) - Forster, Marie-Therese; Lortz, Irina; Seifert, Volker; Senft, Christian
Abstract: OBJECTIVE: Pursuing a profession is an indispensable component of human happiness. The aim of this study was to analyze patients′ professional, socio-economic and psychological outcomes besides their neuro-oncological and functional evaluation after awake surgery for gliomas in eloquent areas. METHODS: The neuro-oncological and functional outcomes of patients with gliomas other than glioblastoma undergoing awake surgery during a period of 5 years were prospectively assessed within our routine oncological follow-up. Repercussions of the disease on their professional status, socio-economic situation, and neurocognitive function were evaluated retrospectively with structured interviews. RESULTS: We analyzed data of 37 patients with gliomas (3 WHO Grade I, 6 WHO grade II, 28 WHO grade III). Gross total and subtotal tumor resections were performed in 20 (54.1%) and 11 (29.7%) patients, respectively, whereas in 7 patients (16.2%) resection had to remain partial. Median follow up was 24.1 months (range: 5–61 months). 31 patients (83.8%) had stable disease, 2 (5.4%) patients suffered from tumor progression and 4 (10.8%) patients died. Prior to surgery, all but one patient were employed. At the time of analysis, 24 (72.7%) of 33 alive patients had resumed their profession. 5 patients (15.2%) were on incapacity pension, 2 patients were on sick leave, and 2 had retired. The median time until return to work following surgery was 5.9 ±4.6 months. Young age (< 40 years) was the only factor statistically significantly associated with the ability to return to work (p< 0.001). CONCLUSION: Despite brain tumor surgery in eloquent regions, the majority of patients with WHO grade II or III gliomas are able to return to work. Employing awake techniques in order to preserve neurological function is of utmost relevance for individual patients′ quality of life and may also decrease the economic burden due to work loss frequently encountered in glioma patients.